A STUDY ON THE IMPLEMENTATION OF WORD CHAIN GAME IN TEACHING VOCABULARY MASTERY - Rhizman Ashary Muhammad; Konder Manurung; Wahyudin Wahyudin (Tadulako University, 2021)
This study was conducted through Library Research method which describes the application of Word Chain Game in Teaching Vocabulary Mastery. Word Chain Game is type of game designed to help players improve their vocabulary mastery. The objectives of this research are to describe the steps on the implementation of Word Chain Game in teaching vocabulary mastery and describe the students’ vocabulary mastery after the implementation of Word Chain Game. The data source were taken from Lewis Carroll (1879) as the primary data and scientific writing on the implementation of Word Chain Game from 2010-2021 as the secondary data. The result of the library research method indicate that there are 5 (five) scientific writing. The result of descriptive analysis show that the implementation of Word Chain Game in five different studies used different steps in implementing the procedures produced by the proponents of the game which consist of 4 steps. 1) The words used must be derived from dictionary. Proper names and words are not permitted. 2) The next word must be formed from the previous word by continuing the word with the last letter in it to form a Chain Word. 3) No word may be used as a Link unless it (or, if an inflection, the word from which it comes) is listed in the following Glossary. When adjectives and adverbs are regularly formed, their comparatives and superlatives are regarded as 'inflections' of the positive form and are not given separately: for example, if the word 'new' is given, it is to be understood that 'newer' and 'newest' are also admissible. However, nouns formed from verbs (such as 'reader' from 'read') are not considered to be so, and may not be used as Links unless they are found in the Glossary. 4) When played in a group, the person who cannot provide the word link is eliminated, and the winner is the only one who remains. When there are two players, the one who makes the most word links wins. One of them ask the students to write, spell, and pronounce the word. Two of them just ask the students to write the word, and other researchers only ask the students to pronounce the word. The vocabulary mastery of EFL students improved after the implementation of Word Chain Game in the classroom. According to the findings, it provides an interesting method for vocabulary building skill and strategies, word memorization, word list recall or vocabulary recognition, and group work. It is conclude that using Word Chain Game in teaching vocabulary is effective. In other words, differences in the teaching procedures do not negatively impact the students vocabulary mastery.